1993
DOI: 10.1007/bf00171534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cocaine on human nasal mucosa

Abstract: The effects of cocaine on the contractile response of isolated human nasal mucosal blood vessels to field stimulation and methoxamine were investigated. Results showed that cocaine antagonized methoxamine and inhibited field stimulation. The drug increased resting tension in human nasal mucosa in vitro through direct actions and potentiated mucosal contractions by norepinephrine and epinephrine. The study indicated that high concentrations of cocaine may actually antagonize alpha-adrenoceptors, but these conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Our results also showed that capsaicin could potentiate the effect of NE on nasal mucosa. But unlike the effects of cocaine, capsaicin lacked a direct action on human nasal mucosa in vitro [13]. Both methoxamine and NE are ·-adrenergic agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that capsaicin could potentiate the effect of NE on nasal mucosa. But unlike the effects of cocaine, capsaicin lacked a direct action on human nasal mucosa in vitro [13]. Both methoxamine and NE are ·-adrenergic agonists.…”
Section: Discussionmentioning
confidence: 99%
“…1 Vasoconstriction is a well-known local sympathetic effect of cocaine that may lead to ischemia, inflammation, ulceration and ultimately necrosis of the nasopharyngeal structures implicated by snorting cocaine. 2 Nasal septal perforation is present in 4.8% of abusers, making it the most common complication of cocaine abuse. 3 Chronic cocaine use may contribute to larger lesions and further destruction of the surrounding osteocartilaginous structures.…”
Section: Oronasal Fistula With Palatal Involvement Secondary To Cocaimentioning
confidence: 99%
“…Cocaine potentiates the injected epinephrine, increasing the possibility of toxic side effects. 11 Anderhuber et al found that even though systemic absorption of locally injected vasoconstrictors occur, adrenalin-related side effects during FESS are extremely rare when the patient is in a monitored setting. 12 Several other studies have described alteration of hemodynamic states after the injection of local anesthetic containing epinephrine.…”
Section: Part IImentioning
confidence: 99%